2001
DOI: 10.1074/jbc.m101983200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein Kinase CK2, Extracellular Signal-regulated Kinase 2, and Protein Phosphatase 2A on a Phosphatidic Acid-preferring Phospholipase A1

Abstract: A soluble, phosphatidic acid-preferring phospholipase A1, expressed in mature bovine testes but not in newborn calf testes, may contribute to the formation or function of sperm. Here we incubated a recombinant preparation of the phospholipase in vitro with several enzymes including protein kinase CK2 (CK2), extracellular signal-regulated kinase 2 (ERK2), and protein phosphatase 2A (PP2A) to identify effects that might be of regulatory importance in vivo. Major findings were that 1) CK2 phosphorylated the phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Global localization analysis has suggested that the YOR022c protein is localized in mitochondria (46). These findings combined with our results and the results of others (24,25,47, and this study) suggest that PA-PLA 1 family proteins appear to be localized in diverse subcellular compartments and may be involved in various biological processes.…”
Section: Depletion Of P125 Affects the Distribution Of Er Exit Sites supporting
confidence: 79%
“…Global localization analysis has suggested that the YOR022c protein is localized in mitochondria (46). These findings combined with our results and the results of others (24,25,47, and this study) suggest that PA-PLA 1 family proteins appear to be localized in diverse subcellular compartments and may be involved in various biological processes.…”
Section: Depletion Of P125 Affects the Distribution Of Er Exit Sites supporting
confidence: 79%
“…The amino acids that are preceded by a p are the amino acids that were phosphorylated. The details regarding the methods used to reveal the sequence and the phosphorylation sites are found in the papers published by Han et al [29] and Han et al [30], respectively. though the 8-br-cAMP and P4 have a similar impact on cell viability, treatment with P4 does not increase PKA activity, as assessed by the phosphorylation of cAMP response element binding protein (CREB) [32].…”
Section: Discussionmentioning
confidence: 99%
“…To determine which site or sites were phosphorylated, the 14-3-3 spot was dissected from three gels obtained from P4-treated lysates and the spots pooled into a single sample. This sample was then analyzed for phosphorylated amino acids as outlined by Han et al [30]. This work was done at the Proteomics and Biological Mass Spectrometry Core Facility (University of Connecticut Health Center, Farmington, CT).…”
Section: Two-dimensional Electrophoresis and Proteomic Analysismentioning
confidence: 99%
“…36) CkII substrates are dephosphorylated by Pp2A (37). In the case of c-myc, this dephosphorylation promotes degradation by the ubiquitin͞proteasomal pathway (37). Erk substrates are also dephosphorylated by Pp2A (37).…”
Section: Generating a Database Of Mrnas Enriched In Siepsmentioning
confidence: 99%
“…SiEP express Ppp2cb mRNA (encodes the ␤ isoform of the catalytic subunit of the protein phosphatase 2A complex; ref. 36) CkII substrates are dephosphorylated by Pp2A (37). In the case of c-myc, this dephosphorylation promotes degradation by the ubiquitin͞proteasomal pathway (37).…”
Section: Generating a Database Of Mrnas Enriched In Siepsmentioning
confidence: 99%